Structure and Properties of Biodegradable Polymers: Rolling Effect in Poly (butylene succinate) Sheets - Jose-Roberto, Vega-Baudrit (2004)
Sheets made from poly (butylene succinate) (PBS) were prepared by extrusion. They have been studied under uniaxial drawing as a function of the draw condition. Changes in molecular orientation and crystallinity were investigated using the criteria of differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), tensile testing, sonic modulus, X-ray diffraction, density, birefringence and measurements of % Haze. Rolling improved the thermo-mechanical and dynamic properties of extruded sheets as a result of changes in molecular orientation and crystallinity.